The effect of governance modes and relatedness of external business development activities on innovative performance - Keil, Thomas; Maula, Markku; Schildt, Henri; Zahra, Shaker A. (Strategic management journal, 2008)
This study examines how different governance modes for external business development activities and venture relatedness affect a firm's innovative performance. Building on research suggesting that interorganizational relationships enhance the innovative performance of firms, we propose that governance modes and venture relatedness interact in their effect on innovative performance. Analyzing a panel of the largest firms in four information and communication technology sectors, we find that degree of relatedness for corporate venture capital investments, alliances, joint ventures, and acquisitions influences their impact on innovative performance.